The Role of Receptor-Interacting Serine/Threonine-Protein Kinase 1 (RIPK1) in CD4+ T Cell Necroptosis in HIV Patients: A Narrative Literature Review - Siregar, Asima Juliyana; Harun Hudari (HM Publisher, 2024)
The human immunodeficiency virus (HIV) remains a global health challenge, with its ability to deplete CD4+ T cells, leading to acquired immunodeficiency syndrome (AIDS). While apoptosis has been extensively studied in CD4+ T cell depletion, recent research has highlighted the significant role of necroptosis, a regulated form of necrosis, in this process. Receptor-interacting serine/threonine-protein kinase 1 (RIPK1) has emerged as a central player in necroptosis, regulating both cell death and inflammatory responses. This review delves into the intricate mechanisms by which RIPK1 orchestrates necroptosis in CD4+ T cells during HIV infection. We explore the structural intricacies of RIPK1, its interactions with other signaling molecules, and the downstream events that culminate in necroptotic cell death. Additionally, we discuss the therapeutic potential of targeting RIPK1 to mitigate CD4+ T cell loss and control HIV disease progression. Understanding the multifaceted role of RIPK1 in HIV-induced necroptosis may pave the way for novel therapeutic interventions to combat this devastating disease.